PELATIHAN PENGELOLAAN KEUANGAN DESA - Delfi Panjaitan; Desy Lesmana; Martha Rianty; Mutiara Maimunah; Weny Putri (Jurnal Abdimas Musi Charitas, 2017)
Training in the Service of Universitas Katolik Musi Charitas on Odd semester of 2016/2017 is the training that is based on Law No. 6 Year 20014 on the village. Act and these regulations then we specialize more on the Regulation of the Minister of the Interior of the Republic of Indonesia Number 114 of 2014 on Guidelines for Rural Development in the form of training preparation of the Medium Term Development Plan Rural (Rural Development Plan) and the Government Work Plan Village. Training is given in a simple, detailed, and requires reciprocal (feedback) and activeness of the participants. It is expected that they can immediately put into practice and benefit from this training.